Wear resistance of nanostructured Cr-based WC hardmetals sintered by spark plasma sintering. (January 2020) - Deng, Xiangxing; Cinca, Núria; Garbiec, Dariusz; Torralba, José Manuel; García-Junceda, Andrea
Abstract: Nanostructured Cr-based WC hardmetals are successfully sintered by spark plasma sintering. The wear behaviour of these Cr-based WC hardmetals with different C contents ranging from 5.57 wt% to 6.91 wt%, is evaluated performing sliding wear tests under two different wear conditions. This work analyses the influence of the C content on the wear performance through the study of the phase formation and WC grain size. The Cr-based hardmetal with 5.57 wt% C content exhibits a lower wear rate than Co-based WC hardmetals tested under similar dry ball-on-plate wear conditions, even considering that these Co-based WC hardmetals have higher WC content (90 wt%) than Cr-based WC hardmetals (83.2 wt%). The combination of a nanosized WC grain and the avoidance of brittle (Cr, Fe)7 C3 or soft graphite phases leads to a superior wear performance. Thus, the use of Cr-based binders in the hardmetal industry, alternatively to Co-based binders, is promising in applications in which high wear resistance is needed. Highlights: The paper investigates the wear behaviour of nanocrystalline Cr-based WC hardmetals sintered by spark plasma sintering. Cr-based hardmetals have achieved a superior wear resistance than Co-based WC hardmetals under a similar testing conditions. Cr-based WC hardmetals have a bright future in the cutting tool industry due to their high wear resistance and low cost.